1998
DOI: 10.1016/s0039-6028(98)00074-0
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate interactions of CO chemisorbed on Pt(111)

Abstract: We show that the observed repulsive interaction between CO molecules on the Pt(111) surface can be explained by the coupling of the Pt-CO separation with Pt-Pt coordinates in the substrate. The observed long range of the interaction and the non-monotonic distance dependence are reproduced. The magnitude of the multiphonon decay of the Pt-CO vibration calculated in this model is also in agreement with experiment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…38 In a very recent theoretical ͑augmented plane-wave͒ work 39 P. J. Feibelman et al have analyzed atop and threefold bonding of CO to Pt͑111͒. They presented Pt͑111͒ and its vicinals by slabs from four to six layers with coverage of 1/3, 1/4, and 1/12 monolayer ͑ML͒.…”
Section: What Is Known For the System Co At Pt"111… So Far?mentioning
confidence: 99%
“…38 In a very recent theoretical ͑augmented plane-wave͒ work 39 P. J. Feibelman et al have analyzed atop and threefold bonding of CO to Pt͑111͒. They presented Pt͑111͒ and its vicinals by slabs from four to six layers with coverage of 1/3, 1/4, and 1/12 monolayer ͑ML͒.…”
Section: What Is Known For the System Co At Pt"111… So Far?mentioning
confidence: 99%
“…Scanning tunneling microscopy, low energy electron diffraction, and infrared adsorption experiments have shown that in ultrahigh vacuum conditions CO adsorbs on top sites exclusively at low coverages and forms a c͑4 ϫ 2͒ top-bridge overlayer at half monolayer coverage. [13][14][15][16][17][18][19][20][21][22] This paper presents a study of the adsorption of CO at 100 K on cerium-platinum surface alloys on Pt͑111͒. The used surface analysis techniques are temperature programmed desorption, low energy electron diffraction, and x-ray photoelectron spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The reconstruction of metal surfaces, including the formation of small metallic clusters, has been observed in many experiments of CO molecules adsorbed on Pt surface. [30][31][32][33] The oxocarbons range from C 2 species to C 9 species, and no C 5 and C 8 species are observed. However, one C 5 O 5 is formed in the Pt 55 (CO) 80 -II.…”
Section: Stabilities Of Oxocarbons Adsorbed On Pt Cluster At High Co mentioning
confidence: 99%